2021
DOI: 10.3390/app11199079
|View full text |Cite
|
Sign up to set email alerts
|

Green Shipping—Multifunctional Marine Scrubbers for Emission Control: Silencing Effect

Abstract: Scrubber systems abate the sulphur oxide emissions of engines when cheap fuel oils that are high in sulphur content are employed as combustibles. However, the ships with these voluminous devices installed on board is space demanding. This work analyses the feasibility of incorporating the acoustic abatement of the exhaust gas noise functionality into the scrubber design to provide a combined scrubber–silencer system. For this purpose, a finite element analysis is performed on a simple expansion chamber, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The use of a scrubber on ships to mitigate exhaust gases is also an attractive choice from an economic perspective compared to marine gas oil [17]. In addition, Kyaw Oo D'Amore et al [18] have shown that scrubbers with targeted design can also have a silencer function.…”
Section: Research Background / Pregled Istraživanjamentioning
confidence: 99%
“…The use of a scrubber on ships to mitigate exhaust gases is also an attractive choice from an economic perspective compared to marine gas oil [17]. In addition, Kyaw Oo D'Amore et al [18] have shown that scrubbers with targeted design can also have a silencer function.…”
Section: Research Background / Pregled Istraživanjamentioning
confidence: 99%
“…When energy efficiency was investigated in a container terminal [1] it was concluded that there was a mutual interest for cooperation between the transport company and the terminal operator to mitigate truck congestion. When energy efficiency is achieved for onboard processes fuel reduction is obtained, but its emissions are still contaminated; more research papers aimed to reduce this effect using optimised scrubbers [2] to achieve a scrubber-silencer system. With the aim to reduce the emissions on board, different works aimed to analyse new combustibles like LNG or cold ironing [3,4] or electrical batteries [5], and other researchers propose the modification of ship [6] and port channels [7].…”
Section: New Procedures For Maritime Sustainabilitymentioning
confidence: 99%
“…In return for this growth, the environmental impact of intensive maritime operationsin particular, the pollutants emitted by ship exhaust gasescan no longer be ignored . The current initiatives, which focus on the development of ship-specific gas scrubbers, are an example of progressive steps toward an environmentally friendly maritime industry . Reflecting the growth of the global economy and trade activities, global seaborne trade has grown considerably over the past two decades .…”
Section: Introductionmentioning
confidence: 99%
“…2 The current initiatives, which focus on the development of ship-specific gas scrubbers, are an example of progressive steps toward an environmentally friendly maritime industry. 3 Reflecting the growth of the global economy and trade activities, global seaborne trade has grown considerably over the past two decades. 4 According to the United Nations Conference on Trade and Development (UNCTAD) held in 2020, international maritime trade has grown from more than 7500 million tons in 2006 to ∼11 billion tons in 2019; with the exception of the 4.2% contraction in the 2020 annus horribilis growth rate due to the recession/ pandemic (Figure 1).…”
Section: Introductionmentioning
confidence: 99%